New parameters on the hematology analyzer XN‐10 (SysmexTM) allow to distinguish childhood bacterial and viral infections. (30th August 2016) - Henriot, I.; Launay, E.; Boubaya, M.; Cremet, L.; Illiaquer, M.; Caillon, H.; Desjonquères, A.; Gillet, B.; Béné, M. C.; Eveillard, M.
Summary: Introduction: Complete blood counts (CBC) performed for infected children admitted for fever mostly disclose leukocytosis. Yet, the recently developed XN‐10 ® provides novel CBC parameters which could be useful to ascertain infection and discriminate between bacterial and viral etiologies. These were the main objectives of the study presented here. Methods: Blood samples from 90 children, 1 month to 5 years old, admitted to an emergency unit for fever benefited from a CBC, C‐reactive protein, and procalcitonin assays. For 58, a bacterial infection was documented while a viral cause was disclosed for 32. Concomitantly, 30 healthy children of the same age range were selected as a control group. Results: Complete blood counts parameters and leukocyte differentials allowed to statistically significantly disclose infection, compared to reference children, in the age group of 1–5 years old. Among the eight novel discriminant parameters, a particular interest appeared for Neutr‐RI and Delta‐He. They both were successfully incorporated in a score together with age and immature granulocytes (IG). ROC curves and AUCs were calibrated using a Hosmer–Lemeshow test. Moreover, novel lymphocyte parameters allowed to segregate bacterial and viral infections in the whole group of 90 febrile children. Conclusion: Complete blood counts is the most broadly performed rapid laboratory investigation. Here, we show that XN‐10 ® provides complementary information allowing to confirm infection in febrile children, moreover discriminating between bacterial or viral origin.